PELATIHAN PENGELOLAAN KEUANGAN KELUARGA PADA MASYARAKAT DESA PURWODADI KABUPATEN MALANG - Ika Rinawati Ika; Anas M. Yusuf Azwar (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2022)
Proper family financial management can create a healthy family financial condition so that the family avoids a financial deficit. Finance with this healthy condition is a financial condition that is able to bear the needs of both current needs and future needs, because we never know what calamities will occur in the future as well as the need for emergency costs that we must spend. The methods used in this PkM activity are socialization, training and participant surveys. The results of this PkM activity show that the people of Purwodadi village are very enthusiastic and willing to implement financial management in every family need. In addition to the ability to arrange structured management, the community is also able to carry out financial evaluations at the end of the month, this is done to see if the financial condition of their families is healthy or not. So that the financial holder, in this case the housewife, can determine the follow-up steps to improve the financial health of her family Keywords: Training ; Financial Management ; Family